2011
DOI: 10.2225/vol14-issue5-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrates and reaction conditions on production of cyclodextrins using cyclodextrin glucanotransferase from newly isolated Bacillus agaradhaerens KSU-A11

Abstract: The effects of reaction conditions on cyclodextrins (CDs) production by CGTase from newly isolated Bacillus agaradhaerens KSU-A11 is reported. Among six types of starch tested, potato starch gave highest starch conversion into CDs. In addition, CDs yield was about three fold higher when using gelatinized potato starch in comparison to raw starch. The total CDs production was increased with increasing pH, showing maximum starch conversion at pH 10. Furthermore, the proportion of γ-CD was relatively higher under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
5
0
3
Order By: Relevance
“…Both values were very similar to those obtained in this study. On the other hand, Ibrahim et al ( 2011 ) reported that the CGTase from B. agaradhaerens was purified in three steps, with a recovery of 26% and twice as much specific activity when compared to that observed in this study. After 3 months, the purified CGTase stored at −4°C kept 85% of its biological activity.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Both values were very similar to those obtained in this study. On the other hand, Ibrahim et al ( 2011 ) reported that the CGTase from B. agaradhaerens was purified in three steps, with a recovery of 26% and twice as much specific activity when compared to that observed in this study. After 3 months, the purified CGTase stored at −4°C kept 85% of its biological activity.…”
Section: Discussionsupporting
confidence: 45%
“…The CGTase shows a Mr similar to other CGTases such as the produced in SmF by Bacillus sp. (69 kDa) and B. firmus (80 kDa) using CS as carbon source (Suntinanalert et al, 1997 ; Pishtiyski et al, 2008 ; Savergave et al, 2008 ; Ibrahim et al, 2011 ). However, there are some reports on CGTases with different Mr, such as that of Paenibacillus macerans grown with CS where its Mr was 114 kDa (Urban et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors obtained the best results with corn starch and concluded that starches from different sources can affect the production of CD and that this could be due to differences in the physical structure of the starch granules and their properties. Ibrahim et al used starches from various sources, including corn, potato, sago, rice, and cassava and obtained the highest CD conversion with potato starch (38.7%). These authors found no differences in the α‐:β‐:γ‐CD relation obtained by varying the starch source.…”
Section: Resultsmentioning
confidence: 99%